2019
DOI: 10.1080/19490976.2019.1667723
|View full text |Cite
|
Sign up to set email alerts
|

Enteric bacteria induce IFNγ and Granzyme B from human colonic Group 1 Innate Lymphoid Cells

Abstract: Group 1 Innate Lymphoid Cells (which include Natural Killer cells and ILC1s) aid in gut antibacterial defense through the production of IFNγ, which is critical for mobilizing protective responses against enteric pathogens. When intestinal epithelial barrier integrity is compromised, commensal bacteria are likely to translocate from the gut lumen into the lamina propria. Few studies have addressed the mechanisms by which commensal bacteria impact the function of gut Group 1 ILCs, especially ILC1s. Utilizing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
0
24
1
Order By: Relevance
“…In response to the enhanced release of IL-12p70, IL-18, and IL-1β by local myeloid dendritic cells (DCs), intestinal ILC1s are able to secrete increased levels of the pro-inflammatory cytokines IFN-γ and TNF-α and thus relevantly support the mucosal immune response against bacterial intruders. This was true for gram-negative commensals and pathogens, e.g., Acinetobacter junii and Salmonella typhimurium, as shown in in vitro cocultures of human ILC1s and lamina propria mononuclear cells (LPMCs) (79). Without proper regulation of this response, chronic inflammation can be established.…”
Section: Local Regulation Of Human Helper Ilc1smentioning
confidence: 99%
“…In response to the enhanced release of IL-12p70, IL-18, and IL-1β by local myeloid dendritic cells (DCs), intestinal ILC1s are able to secrete increased levels of the pro-inflammatory cytokines IFN-γ and TNF-α and thus relevantly support the mucosal immune response against bacterial intruders. This was true for gram-negative commensals and pathogens, e.g., Acinetobacter junii and Salmonella typhimurium, as shown in in vitro cocultures of human ILC1s and lamina propria mononuclear cells (LPMCs) (79). Without proper regulation of this response, chronic inflammation can be established.…”
Section: Local Regulation Of Human Helper Ilc1smentioning
confidence: 99%
“…ILC1s are predominantly distributed within the intestinal lamina propria and participate in resisting bacteria by secreting IFN‐γ 38 . After exposure to pathogenic bacteria, lamina propria mononuclear cells (LPMC) activate ILC1s to release IFN‐γ, which in turn resist bacterial invasion 79 . Besides, IL‐22‐secreting ILC3s promote the secretion of antimicrobial peptides, lipocalin and mucus to prevent the invasion of bacteria 80 .…”
Section: Ilcs In the Intestinesmentioning
confidence: 99%
“…ILC1, including NK cells, are mainly involved in the defense against tumors and intracellular pathogens such as viruses. Information about the interaction of ILC1 with bacteria had so far been limited, but has become better understood because of several recent reports [ 1 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A human study in which colonic lamina propria-derived ILC1 were exposed to commensal gut bacteria, interestingly showed that only Gram-negative bacteria induced the production of IFN-γ.…”
Section: Infections Of the Gastrointestinal Tractmentioning
confidence: 99%
“…A human study in which colonic lamina propria-derived ILC1 were exposed to commensal gut bacteria, interestingly showed that only Gram-negative bacteria induced the production of IFN-γ. CD11c + myeloid dendritic cells (mDC) mediate ILC1 stimulation by releasing the cytokines IL-12p70, IL-18, and IL-1β, resulting in ILC1-derived production of granzyme B and IFN-γ [ 35 ]. Moreover, in vitro experiments indicated that IFN-γ could promote the translocation of Escherichia coli (E.coli) due to cytokine-dependent tight junction disruption [ 36 ].…”
Section: Infections Of the Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation